2017
DOI: 10.1111/ajag.12446
|View full text |Cite
|
Sign up to set email alerts
|

Meaningful use of computers has a potential therapeutic and preventative role in dementia care: A systematic review

Abstract: Early findings are promising, but more rigorous studies are required to examine the nature of the relationship between computer use and dementia risk, and the potential of computer activities to improve outcomes for people experiencing cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…Our finding is consistent with a study using the English Longitudinal Study of Aging (ELSA) cohort which showed that internet users had better cognitive performance measured by delayed recall compared with internet nonusers [13]. Other results of a protective association between internet use and cognitive function were also reported in other developed countries [12-16]. Although the exact mechanism is not clear, a potential theoretical pathway may be that internet access imparted a reserve against the expression of cognitive impairment [10,26,27].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding is consistent with a study using the English Longitudinal Study of Aging (ELSA) cohort which showed that internet users had better cognitive performance measured by delayed recall compared with internet nonusers [13]. Other results of a protective association between internet use and cognitive function were also reported in other developed countries [12-16]. Although the exact mechanism is not clear, a potential theoretical pathway may be that internet access imparted a reserve against the expression of cognitive impairment [10,26,27].…”
Section: Discussionsupporting
confidence: 91%
“…A growing number of epidemiologic studies have clearly suggested that digital devices, like internet-based instruments, can provide a platform of cognitively stimulating activities which might help to slow the path of cognitive decline in the process of normal aging [10-12]. Longitudinal studies and meta-analyses in developed countries have shown that the use of the internet can be a protective factor for cognitive decline among the older population [13-16]. In the context of China, there has been a marked increase in internet access among mid-aged and elderly populations [17], although the national data on internet use is limited.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a mounting evidence that the use of ICT may also have a preventive influence on the development or progression of dementia in the elderly population [42,43,44]. As the elderly constitute the major part of the population suffering disabilities, such findings may be a further argument for supporting the use of computer and the Internet by the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were categorized into these age groups as these groupings allowed within-group variation to be minimized. Prior to 3D-MOT training, participants in the 74…”
Section: Agementioning
confidence: 99%
“…A final limitation in this study is the lack of an active control. Current research demonstrates that older adults who spend regular and meaningful time on the computer have a lower risk of developing mild cognitive impairment (MCI) and dementia [74]. Though the mechanism behind this is currently unknown, researchers Krell-Roesch and colleagues [47] attribute computer use with an increased demand for specific technical and manual skills which may have a protective effect against cognitive decline.…”
Section: Limitationsmentioning
confidence: 99%